Inborn errors of IKAROS and AIOLOS - Yamashita, Motoi; Morio, Tomohiro (Current opinion in immunology, 2021)
IKAROS is a pioneer protein of the IKZF family of transcription factors that plays an essential role in lymphocyte development. Recently, inborn errors of IKAROS have been identified in patients with B cell deficiency and hypogammaglobulinemia, and these patients often present with recurrent sinopulmonary infection. Autoimmunity and hematologic malignancies are other characteristic complications seen in the patients with IKAROS deficiency. Missense mutation involving asparagine at the 159th position results in combined immunodeficiency, often presenting with Pneumocystis jirovecii pneumonia. Inborn errors of AIOLOS, HELIOS, and PEGASUS have also been reported in patients with B cell deficiency, Evans syndrome, and hereditary thrombocytopenia, respectively. Here, we briefly review the phenotype and genotype of IKZF mutations, especially IKAROS.